Tumbuhan Obat: Pendekatan Alternatif dalam Pengendalian Nyamuk Aedes aegypti dan Virus Dengue Penyebab Demam Dengue - Ign Joko Suyono; Aditya K. Karim (Jurusan Biologi FMIPA Universitas Cenderawasih, 2012)
Dengue is the most important emerging tropical viral disease of humans in the world today. Aedes aegypti is a major mosquito vector responsible for transmitting many viral diseases and this mosquito that spreads major health problems like dengue fever. The resistance of Ae. aegypti to insecticides is already widespread and represents a serious problem for programmes aimed at the control and prevention of dengue in tropical countries. The search for compounds extracted from medicinal plant preparations as alternatives insecticide for mosquito control is in immediate need. Alternative approach for control Ae. aegypti dan virus dengue using the medicinal plant will be discussed in this paper.Key words: Medicinal plant, Aedes aegypti, dengue fever, dengue haemorragi fever, dengue shock syndrome